2010
DOI: 10.1037/a0021791
|View full text |Cite
|
Sign up to set email alerts
|

The effects of modafinil treatment on neuropsychological and attentional bias performance during 7-day inpatient withdrawal from methamphetamine dependence.

Abstract: The cognitive benefits of modafinil to patients undergoing 7-day inpatient withdrawal from methamphetamine (MA) dependence were examined as part of a double-blind, randomized, placebo-controlled pilot trial. Recent evidence has identified modafinil-related improvements in treatment outcomes for MA-dependent patients; however, the benefits to cognition function, which is critical to treatment success but known to be impaired, has yet to be examined. The first 20 participants recruited to the study were administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 77 publications
0
22
0
1
Order By: Relevance
“…Although this dose has been shown to improve cognitive function in other MA-dependent, psychiatric, and healthy subject samples (Hester et al, 2010;Müller et al, 2004;Turner et al, 2003Turner et al, , 2004aTurner et al, , 2004bWalsh et al, 2004), higher doses (e.g., 400 mg) have been shown to be safe in MA-dependent participants (Heinzerling et al, 2010) and may produce a more pronounced cognitive effect. In addition, compared with our single-dose design, use of a multiple-dose design would have been preferable for the detection of a dose-response relationship between modafi nil and cognitive performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although this dose has been shown to improve cognitive function in other MA-dependent, psychiatric, and healthy subject samples (Hester et al, 2010;Müller et al, 2004;Turner et al, 2003Turner et al, , 2004aTurner et al, , 2004bWalsh et al, 2004), higher doses (e.g., 400 mg) have been shown to be safe in MA-dependent participants (Heinzerling et al, 2010) and may produce a more pronounced cognitive effect. In addition, compared with our single-dose design, use of a multiple-dose design would have been preferable for the detection of a dose-response relationship between modafi nil and cognitive performance.…”
Section: Discussionmentioning
confidence: 99%
“…In a human laboratory study, several acute doses of modafi nil (150, 300, and 450 mg) did not significantly modify inhibitory control in cocaine users (n = 11), although the go/no-go task used in this study may not have been optimized to detect improvements in inhibitory control (Vansickel et al, 2008). In a small, between-subjects, inpatient study, immediate verbal memory was improved in MA-dependent participants receiving modafi nil (200 mg; n = 7) relative to those receiving placebo (n = 7) (Hester et al, 2010), but differences between the groups were not observed on measures of visual memory, processing speed, or verbal fl uency. Last, in a small study of MA-dependent subjects (n = 11; Kalechstein et al, 2010), modafi nil (400 mg) did not have a signifi cant effect on working memory and learning/memory performance across subjects.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…In a small inpatient study, 7 days of modafinil treatment improved immediate verbal memory function in 14 patients with methamphetamine dependence who were undergoing 7-day withdrawal (Hester, Lee, Pennay, Nielsen, & Ferris, 2010). In another study, 3 days of modafinil (400 mg/day) treatment improved working memory function in individuals with methamphetamine dependence (n=11) who had impaired working memory function at baseline (Kalechstein, De La Garza, & Newton, 2010).…”
Section: Treatment Approaches Targeting Cognitive Functionsmentioning
confidence: 99%
“…Modafinil improved verbal memory recall after 5 days of administration (Hester et al, 2010); and modafinil-related improvements in working memory were found in a subgroup of methamphetamine-dependent volunteers with poor baseline performance, as compared with high performers, after 3 days of administration (Kalechstein et al, 2010). In two other studies, a single dose of modafinil was associated with overall improvements in learning performance (Ghahremani et al, 2011), and in inhibitory control and processing speed in a subgroup of methamphetamine-dependent patients with high baseline frequency methamphetamine use, versus a subgroup with low baseline frequency methamphetamine use (Dean et al, 2011).…”
Section: Introductionmentioning
confidence: 97%